مساهمة القرآن والحديث في اللغة العربية - Najib, Aan (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2019)
Allah Almighty establishes through His messenger with clear and wise language. No one speaks fluently like his prophet, including the Hadis which are the words, deeds and stipulations of the Prophet Muhammad. Allah SWT gave him a speech style and taught him Arabic languages ​​and dialects, because Allah Almighty wanted him to be a teacher and guide  for all mankind. The style of the prophet's speech is jami 'mani' (short, solid, interesting). His beautiful speaking style made the Hadis put in second place after the Qur'an. Its superiority cannot be defeated by the great poet or orator that has ever existed. Language is spoken clearly, beautifully, and calmly based on situations and conditions, so it is melodious and digestible for all those who want to learn about Islam and of course there is no choice but to learn Arabic. Therefore, Allah always safeguards Arabic from extinction.